Identifying anticholinergic burden in clinical practice. Issue 3 (23rd March 2021) - Bell, Brian; Avery, Anthony
Abstract : Anticholinergic medications are associated with a wide range of adverse effects to which elderly patients are particularly susceptible. This article discusses the various ways that anticholinergic burden can be measured, how these can be used to help clinicians identify patients at risk from the adverse effects of anticholinergics, and how to address these risks.